Estudo das relações de trabalho e de impacto social nas operações em serviços de venda direta na região Centro Sul do Estado do Paraná - Viante, Robercil (2019)
ABSTRACT This dissertation sought to analyze the work process of door-to-door cosmetics vendors, their remuneration and social needs, based on the work developed by sales operators in a specific company in this sector in the cities of the center-south region of the state of Paraná. The importance of the research is emphasized, since it addresses labor rights, social impacts of informality and the need for work. Thus, the interest in addressing the theme of labor exploitation in cosmetic sales operations, perceptions of social inequality of the activity, aspects of informality and loss of basic labor rights. The central question of the research emphasizes impacts and consequences of loss of labor rights. The objectives were: to analyze the existence of the loss of labor rights and its economic and social consequences in the use of the informal labor force in the practice of direct sales; identify the labor rights omitted by the company in the execution of this activity; to assess the perceptions of labor rights knowledge on the part of the interviewees; and to identify the degree of satisfaction of those involved in relation to informality. The study consisted of a mixed approach (qualitative-quantitative), conducted by a bibliographical research and field survey, through interviews and use of semi-structured questionnaires. Data processing was done through document analysis, content verification, data triangulation and interviews. The results showed that there is an undervaluation of the door-to-door salesperson profession, ignorance of labor laws and social protection, as well as a high degree of informality in the application of the work. It was concluded that the main purpose of this occupation is to supply the immediate financial need of these workers, who seek, in the informal occupation, a form of income supplement for their subsistence.